Directional transport in Rydberg atom arrays via kinetic constraints and temporal modulation - Yupeng Wang; Junjie Wang; Aishik Panja; Xinghan Wang; Qi-Yu Liang (Physical Review Research)
We propose an experimentally feasible scheme to achieve directional transport of Rydberg excitations and entangled states in atomic arrays with unequal spacings. By leveraging distance-dependent Rydberg-Rydberg interactions and temporally modulated laser detunings, our method directs excitation flow without requiring local addressing. Numerical simulations demonstrate robust and coherent transport under experimentally realistic conditions. Additionally, we show that this scheme enables controlled transport of Bell pairs and preserves entanglement during propagation. The approach provides a versatile platform for programmable directional transport, with potential applications in quantum simulation, entanglement distribution, and the design of scalable quantum processors and networks.